The road to micronutrient biofortification of rice: progress and prospects - Bashir, Khurram; Takahashi, Ryuichi; Nakanishi, Hiromi; Nishizawa, Naoko K. (Frontiers in Plant Science, 2013)
Biofortification (Increasing the contents of vitamins and minerals through plant breeding or biotechnology) of food crops with micronutrient elements has the potential to combat widespread micronutrient deficiencies in humans. Rice (Oryza sativa L.) feeds more than half of the world’s population and is used as a staple food in many parts of Asia. As in other plants, micronutrient transport in rice is controlled at several stages, including uptake from soil, transport from root to shoot, careful control of subcellular micronutrient transport, and finally, and most importantly, transport to seeds. To enhance micronutrient accumulation in rice seeds, we need to understand and carefully regulate all of these processes. During the last decade, numerous attempts such as increasing the contents/expression of genes encoding metal chelators (mostly phytosiderophores) and metal transporters; overexpressing Fe storage protein ferritin and phytase were successfully undertaken to significantly increase the micronutrient content of rice. However, despite the rapid progress in biofortification of rice, the commercialization of biofortified crops has not yet been achieved. Here, we briefly review the progress in biofortification of rice with micronutrient elements (Fe, Zn and Mn) and discuss future prospects to mitigate widespread micronutrient deficiencies in humans.